AHNS endocrine surgery section consensus statement on nasopharyngolaryngoscopy and clinic reopening during COVID‐19: How to get back to optimal safe care. Issue 2 (17th November 2020) - Bleier, Benjamin; Workman, Alan; Burks, Ciersten; Maxfield, Alice; Stack, Brendan C.; Nathan, Cherie‐Ann; McCammon, Susan; Varvares, Mark; Schmalbach, Cecelia; Wang, Steven; Califano, Joseph; Shnayder, Yelizaveta; et al.
Abstract: This article provides best practice guidelines regarding nasopharyngolaryngoscopy and OHNS clinic reopening during the COVID‐19 pandemic. The aim is to provide evidence‐based recommendations defining the risks of COVID‐19 in clinic, the importance of pre‐visit screening in addition to testing, along with ways to adhere to CDC guidelines for environmental, source, and engineering controls.